Climate‐driven hydrological variability determines inter‐annual changes in stream invertebrate community assembly. Issue 11 (25th June 2018) - Sarremejane, Romain; Mykrä, Heikki; Huttunen, Kaisa‐Leena; Mustonen, Kaisa‐Riikka; Marttila, Hannu; Paavola, Riku; Sippel, Kalle; Veijalainen, Noora; Muotka, Timo
Abstract : Although flow regime is one of the major drivers of riverine communities, not much is known about how inter‐annual variability and extremes of flow influence community assembly mechanisms. We used data on benthic macroinvertebrates and modelled flow regimes in 23 near‐pristine boreal streams to assess how community assembly mechanisms and species occupancy varied in response to inter‐annual variability in flow conditions across 11 successive years encompassing extreme (both low and high) flow events. A null model approach was used to test whether deterministic or stochastic processes dominated community assembly and how much regional (among‐stream) flow variability contributed to community variability (β‐diversity). Mean daily flow and the greatest rate of flow rise were the strongest flow‐related descriptors of invertebrate community composition. Communities were differentially assembled depending on the direction of change in flow magnitude: in high‐flow years, communities were more similar than expected by chance, while at low flows they tended to be more dissimilar than expected. Beta‐diversity of macroinvertebrate communities was related to among‐stream flow variability only at high flows. Common species correlated strongly with flow variability and contributed most to variation in β‐diversity, suggesting that changes in assembly mechanisms are mainly driven by common species. While homogenization of communities in high‐flow years reflected increased species occupancies and environmental sorting, increased turnover during low flows likely resulted from stochastic extinctions and dispersal limitation. Our findings suggest that extreme hydrological events exert a strong control over stream invertebrate community assembly, and their effect may be even more profound in the future as high and low‐flow spells are expected to occur more frequently, not allowing time for communities to recover.